Actualization of Political Education in Digital Learning to Prevent Radicalism - Hilal Ramdhani; Rayhan Musa Novian (Universitas Muhammadiyah Mataram, 2020)
Radicalism is a problem for the Indonesian people to be able to create a sense of unity and unity in achieving the goals of the state. Efforts have been made, such as de-radicalization by the government, but have been met with resistance from human rights activists. Efforts that are considered more humane are through political education. This study aims to determine political education in tertiary institutions. This study uses a qualitative approach with a case study method at the Indonesian University of Education used in identifying the actualization of political education. The results of the study showed that the prevention of radicalism in the universities could be carried out with early detection of the movement of radical understanding from the top down carried out by outsiders, as well as those carried out from the bottom up by the individual himself exploring radical understanding through various sources so that he himself was infiltrated. Developing an educational model that can prevent a whole design that contains a philosophical foundation.